Investigation on the factors leading to negative attitudes towards mathematics among secondary school students in Tanzania - Emmanuel Deogratias; Aziza Iddi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study investigated the factors contributing to the negative attitudes—often perceived as "hatred"—towards mathematics among secondary school students. A quantitative research approach was adopted, involving a total of 200 student respondents. Data were collected through structured questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS). Findings from the study revealed several key factors influencing students’ negative perceptions of mathematics. These included the use of unengaging and ineffective teaching methods, inadequate support from teachers when students encountered difficulties, peer influence, the perceived complexity of mathematical concepts, challenges related to the language of instruction, scarcity of instructional resources, and the use of punishment in the learning process. To foster a more positive attitude towards mathematics among students, the study recommends enhancing access to adequate learning materials and resources; encouraging collaboration between teachers and parents to promote the value of mathematics education; adopting innovative and interactive teaching techniques; minimizing the use of corporal punishment in schools; and implementing reward-based systems to acknowledge student progress and efforts in mathematics.